Penilaian Pengelolaan Teknologi Informasi Dengan Menggunakan Kerangka Kerja COBIT Pada Domain Deliver & Support - Jolsvi Daely (Jurnal Teknologi Informasi dan Komputer, 2015)
Lack  of  state  support  of  telecommunications  facilities  as  a  branch  of  the  external resistance factor, making PT. Carrefour Indonesia often experience less than the maximum target achievement. Cope with this, companies adapt by strengthening internal factors in order to close the gap caused by external factors. However, the company is difficult to determine in detail the internal factors which need to be strengthened. To that end, research is done on the management of information  technology  to  map  all  the  activities,  based  on  the  framework  COBIT  (Control Objectives for Information and related Technology).The methods used in the research management of information technology, namely: (1) Method  of  Control  Objectives  (Control  Objective,  (2)  Method  of  Analysis  Causal  KPI  (Key Performance Indicator) and KGI (Key Goal Indicator ). The Maturity Model is a method that can be used to assess the scale of maturity in the process of managing an information technology. Based on the research conducted, PT. Carrefour Indonesia has already reached the 3.674; above the  standard  international  average  is  3,000.  But  when  viewed  from  a  predefined  target management is at position 3.915, then the gap created by (0.241) compared to the conditions that exist today. The existence of advice on the issue, expected to be a meaningful  input for PT. Carrefour Indonesia in continuous progress.Keywords: Management, COBIT, Control Objectives, Causal Analysis KPI and KGI, Maturity Model, gap